Validation of Notch-Stress Intensity Factor, Strain Energy Density and Effective Notch Stress approaches in fatigue life assessment of austenitic steel welded joints (Fracture and Structural Integrity, 2026)
The purpose of this work is to validate the N-SIF, SED and ENS approaches for the fatigue design of austenitic stainless steel welded joints. Literature fatigue data for cruciform welded joints, originally expressed in terms of nominal stress, were first re-analysed through a finite element model in terms of N-SIF. The resulting fatigue limit was then used to determine the SED critical radius required for the application of the SED approach. The same dataset was subsequently reprocessed in terms of SED. Finally, a second finite element model was implemented to calculate the ENS values. The N-SIF and SED approaches led to a more unified representation of the fatigue behaviour compared to nominal stress, showing a noticeable reduction in data scatter. In contrast, the ENS method exhibited a significant dispersion for the investigated joints, possibly due to material-specific effects and to the geometric regularisation introduced by the fictitious notch radius. Although the available dataset is limited to root failures in cruciform joints, the results suggest promising applicability of fracture-mechanics-based local approaches to austenitic stainless steel welded joints, while indicating that further validation of the ENS method is required.
Keywords: Austenitic steel welded joints; Notch-Stress Intensity Factor; Strain Energy Density; Effective Notch Stress; Finite element analysis